Top quark phenomena in association with new vector bosons - B, Bayarsaikhan; Ts, Enkhbat; L, Erdenebulgan (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this work, we study collider phenomenology of pair produced new heavy vector bosons further decaying into top quark pair and quartic top, top pair plus bottom pair production in proton-proton collisions at CERN LHC with 13 TeV center of mass energy in the presence of new color octet vector boson. The complete simulation chain analysis from parton to the detector level is done for the pair production, As for the four quark production through pair of the new heavy vector particles is done at the matrix level. In doing so we have preparatory work . The extension of SM is implemented by Mathematica—FeynRule package. Calculations are done by MadGraph5 /+ Phythia6, Delphes / simulation program and results are analysed in ROOT CERN. In conclusion, we compared Standard model extension results with the SM.